Clinical characteristics of haematological malignancy patients diagnosed with leukaemia cutis: Experience of a single centre. (4th November 2014) - Pamuk, Gulsum Emel; Ak, Recep; Tasci, Murat; Harmandar, Ferda; Demir, Muzaffer; Arican, Ozer
Abstract: Background/Objectives: We evaluated the clinical characteristics of patients with haematological malignancies at our centre who were diagnosed with leukaemia cutis (LC). In addition, we describe the spectrum of other skin lesions, including, secondary skin malignancies and nonspecific benign skin lesions in haematological malignancy patients. Methods: We defined 58 skin lesions that developed in 54 inpatients hospitalised in the Department of Haematology, Trakya University Medical Faculty, Turkey. All skin lesions that developed in inpatients between 2006 and 2012 had been evaluated by a dermatologist. The patients' clinical features, skin biopsy results and therapies were obtained from hospital files. The diagnosis of LC was based on clinical features and histopathological examinations of the skin biopsy. Results: There were 11 patients with LC. Six (54.5%) had acute myeloblastic leukaemia. In nine patients (82%), LC was present at the initial presentation. Secondary skin malignancy was detected in 11 patients (five basal cell carcinoma, four Kaposi's sarcoma, one squamous cell carcinoma, one malignant melanoma); and malignancy was present in two patients (18%) at the initial presentation. Nonspecific benign skin lesions, the most frequent of which were drug eruptions, were determined in 32 of our patients. LC had a significantly higher likelihood of being present at initial presentation than other skin lesions ( P  < 0.01). The median survival in LC patients was quite short (4.5 months). Conclusions: LC was usually diagnosed at the initial presentation of the patient or during the early course of the disease. Having LC was a poor prognostic factor.